Clinico-epidemiological study among leprosy patients at Leprosy Referal Center Buldana: a retrospective study - Rathod, Kisan V.; Masare, Monika S.; Thakre, S. S. (International Journal Of Community Medicine And Public Health, 2025)
Background: Leprosy has been officially eliminated from India since December, 2005; still, there are districts and blocks reporting high prevalence indicating ongoing transmission. The present study aimed at determining the current clinical profile of leprosy from a tertiary level hospital Leprosy Referral Centre (LRC) Buldana, Khamgao, Malkapur. Methods: A retrospective, cross-sectional study was carried out on patients diagnosed and registered in the leprosy clinic of 3 LRC of Buldana district from 18 April to 31 December 2022. Data regarding demographic details, clinical features, treatment started and complications was analysed. Results: A total of 904 patients were registered over distribution of three LRC a 6-year period, with M: F ratio of 1.3:1. 3.33% were children (≤14 years). Multibacillary leprosy was the most common clinical type (62.6%). Borderline tuberculoid leprosy was the most frequent morphologic type, seen in 44.6% followed by tuberculoid 25.33%, borderline-borderline (3.33%), borderline lepromatous (11.33%), lepromatous leprosy (8.66%), pure neuritic (2.00%), histoid and indeterminate leprosy (2.66%). 10.06 % patients presented in reaction. World Health Organization (WHO) grade II deformities were diagnosed in 0.66% with claw hand being the most common paralytic deformity. Conclusions: Our study offers insight into the current status of the disease in an area of otherwise low prevalence. It is seen that multibacillary disease, leprosy reactions and deformities are commonly seen. Buldana has unique demography with a high degree of migrant workers, presenting to our centre (near border location) could be a possible contributing factor towards these aberrations. It highlights the need for continuation of targeted leprosy control activities and Surveillance active case detection.